Amniotic membrane/ umbilical cord particulate injection for achilles tendinopathy with or without a partial tear - Michael J. Chin, DPM; Kathryn LaViolette, DPM (Foot & Ankle Surgery: Techniques, Reports & Cases, 2022)
Background: Achilles tendinopathy is a significant cause of disability among American adults. Among these tendinopathy cases, 4-23% will also have concurrent partial tendon tears. For these conditions, non-surgical conservative treatment has a wide range of reported success. This study investigated the alternative use of amniotic membrane/umbilical cord particulate (AMUC) injection in patients with Achilles tendinopathy with or without partial tendon tear. Method: A single-center, retrospective study was conducted on Achilles tendinopathy patients with or without a partial tendon tear and received AMUC injection between January 2016 and January 2021. Pain was evaluated before and after treatment, and measured on a 11-point numerical rating scale, where 0 was no pain and 10 was worst imaginable pain. Usage of pain medication and complications was also reported. Results: Ten Achilles tendinopathy patients (aged 61.3 ± 11.3 years) with (n=3) or without (n=7) partial tendon tear were included in the analysis. The cohort's average baseline pain score was 4.8 ± 1.2 despite the majority (n=9) of patients receiving prior conservative treatment over a duration of 78.3 ± 77.6 days. After AMUC injection, the pain significantly decreased to 1.7 ± 1.9 at 1 month and 1.1 ± 1.4 at 3-months (p<0.01) post-treatment. Four patients who had previously used narcotic pain medication discontinued use within 3-months after treatment. There were no treatment-related complications. Conclusion: Use of injectable AMUC may safely provide pain relief in Achilles tendinopathy patients with or without partial tendon tear. Additional comparative studies with larger treatment groups are warranted to validate these findings.